Low prevalence of viable Toxoplasma gondii in fresh, unfrozen, American pasture-raised pork and lamb from retail meat stores in the United States. (March 2020) - Dubey, Jitender P.; Hill, Dolores E.; Fournet, Valsin; Hawkins-Cooper, Diane; Cerqueira-Cézar, Camila K.; Murata, Fernando H.A.; Verma, Shiv K.; Kwok, Oliver C.H.; Rani, Surabhi; Fredericks, Jorrell; Adams, Brandon; Jones, Jeffrey L.; et al.
Abstract: In a national survey of fresh, unfrozen, American pasture-raised lamb and pork, the prevalence of viable Toxoplasma gondii was determined in 1500 samples selected by random multistage sampling (750 pork, 750 lamb) obtained from 250 retail meat stores from 10 major geographic areas in the USA. Each sample consisted of a minimum of 500 g of meat purchased from the retail meat case. To detect viable T. gondii, 50 g meat samples of each of 1500 samples were bioassayed in mice. Viable T. gondii was isolated from 2 of 750 lamb samples (unweighted: 0.19%, 0.00–0.46%; weighted: 0.04%, 0.00–0.11%) and 1 of 750 pork samples (unweighted: 0.12%, 0.00–0.37%; weighted: 0.18%, 0.00–0.53%). Overall, the prevalence of viable T. gondii in these retail meats was very low. Nevertheless, consumers, especially pregnant women, should be aware that they can acquire T. gondii infection from ingestion of undercooked meat. Highlights: First national survey of T. gondii in naturally raised lamb and pork in USA. 1500 (750 pork, 750 lamb) samples of natural meat USA tested for viable T. gondii. Viable T. gondii isolated from 2 of 750 lambs and 1 of 750 pork. Although the risk was low, meats should be cooked thoroughly before consumption.